Peripheral Neuropathy and Tear Film Dysfunction in Type 1 Diabetes Mellitus - Stuti L. Misra; Dipika V. Patel; Charles N. J. McGhee; Monika Pradhan; Dean Kilfoyle; Geoffrey D. Braatvedt; Jennifer P. Craig (Journal of Diabetes Research)
Purpose. To compare tear film metrics in patients with type 1 diabetes mellitus (DM) and healthy controls and investigate the association between peripheral neuropathy and ocular surface quality. Methods. Dry eye symptoms were quantified in 53 patients with type 1 DM and 40 age-matched controls. Ocular examination included tear film lipid layer thickness grading, tear film stability and quantity measurement, and retinal photography. DM individuals additionally underwent a detailed neuropathy assessment. Results. Neither mean age nor dry eye symptom scores differed significantly between the DM and control groups (P=0.12 and P=0.33, resp.). Tear lipid thickness (P=0.02), stability (P<0.0001), and quantity (P=0.01) were significantly lower in the DM group. Corneal sensitivity was also reduced in the DM group (P<0.001) and tear film stability was inversely associated with total neuropathy score (r=-0.29, P=0.03). Conclusion. The DM group exhibited significantly reduced tear film stability, secretion, and lipid layer quality relative to the age-matched control group. The negative correlation between tear film parameters and total neuropathy score suggests that ocular surface abnormalities occur in parallel with diabetic peripheral neuropathy.